JURIDICAL REVIEW OF CRIMINAL ACTS INTERNET BASED SCAM (Studi Kasus Putusan PN Surabaya Nomor.1791/Pid.Sus/2019/PN.Sby) - Devita Dyah Al Fanni; Shinta Rukmi Budiastuti; Esti Aryani (Wacana Hukum, 2021)
Crime in cyberspace knows no boundaries and time so that the handling is different from ordinary conventional crimes one Cybercrime crime is carding crime. This crime canbe calledalso as a credit cardwiretap which is classified as a moderncrime. This study aims to examine the form of accountabilityinternet-based fraud perpetratorsin the decision Number Judges'Considerations in make a verdict on the internet-based fraudcrime Decision Number 1791/2019 / Pid.sus / PN.Sby.his study uses the data analysis method used in this study is a normative qualitative analysis method. The data collection method uses the library research method. This method used to collect secondary data, several instrumentsthe collection used is literature study.based fraud in verdicts Number.1791 / 2019 / Pid.sus / PN.Sby.supporting factors in enforcementcarding crime, namely witness statements, expert statements, evidence. The defendant was charged under Article 30 paragraph (2) in conjunction with Article 46 paragraph (2) RI Law No. 19 of 2016 concerning amendments to Law of the Republic of Indonesia No. 11 of 2008 regarding Information and Electronic Transactions, Article 30 paragraph (2) in conjunction with Article 46 paragraph (2) RI Law No. 19 of 2016 concerning amendments to Law of the Republic of Indonesia No. 11 of 2008 regarding Information and Electronic Transactions in conjunction with Article 56 paragraph (2)ofthe Criminal Code and Law Number 8 of 1981. Judges' Legal Considerations in applying criminalprovisions against the criminal perpetrator in the case of decision Number.1791/2019 / Pid.sus / PN.Sby, The defendant was sentenced by the Panel of Judges respectively for the Defendant 1 5 (five) months and 15 (fifteen) days and a fine of Rp.3,000,000 (three million rupiah) and for Defendant II for 6 (six) months and 15 (sixteen) days and a fine of IDR 3,000,000 (three million rupiah). Because it has been legally proven to have committed a carding crime as regulated in the Law on Information and Electronic Transactions.